Pengaruh Motivasi Kerja terhadap Kinerja Karyawan PT. Jasa Raharja Cabang DKI Jakarta - Setya Wahyu Fajar (Arus Jurnal Pendidikan, 2023)
Human resources are one element of the company and have a very important role in activities within the company. The important thing in human resource management is about employee performance One of the factors that affect performance is motivation. The higher the motivation, the higher the performance of the employees. This study aims to determine the effect of work motivation on employee performance at PT. Jasa Raharja DKI Jakarta Branch. This study used quantitative methods. With a total sample of 81 employees of PT. Jasa Raharja DKI Jakarta Branch. The scale used for employee performance theory of Mathis & Jackson (2006) is quality of work, quantity, punctuality, absenteeism, ability to work together. While the scale for work motivation uses theories from Herzbeg (2008), namely motivator factors and hygiene factors. The data collection method uses scale and sample selection with the type of Non probality sampling with total sampling techniques. The data analysis method uses simple linear regression analysis. Data processing is done using the program SPSS Version 26.0 for windows. The result of the correlation or relationship value (r) is 0.451. Based on the analysis that has been done, it is known that Ho was rejected and Ha was accepted. The results showed that there was a significant influence that was highly correlated and had a positive relationship between work motivation and employee performance.